Pulsed Dynamic Water Electrolysis: Mass Transfer Enhancement, Microenvironment Regulation, and Hydrogen Production Optimization - Zhang, Xuewei; Zhou, Wei; Meng, Xiaoxiao; Huang, Yuming; Yu, Yang; Zhao, Haiqian; Wang, Lijie; Sun, Fei; Gao, Jihui; Zhao, Guangbo (Nano-Micro Letters, 2026)
Pulsed dynamic electrolysis (PDE), driven by renewable energy, has emerged as an innovative electrocatalytic conversion method, demonstrating significant potential in addressing global energy challenges and promoting sustainable development. Despite significant progress in various electrochemical systems, the regulatory mechanisms of PDE in energy and mass transfer and the lifespan extension of electrolysis systems, particularly in water electrolysis (WE) for hydrogen production, remain insufficiently explored. Therefore, there is an urgent need for a deeper understanding of the unique contributions of PDE in mass transfer enhancement, microenvironment regulation, and hydrogen production optimization, aiming to achieve low-energy consumption, high catalytic activity, and long-term stability in the generation of target products. Here, this review critically examines the microenvironmental effects of PDE on energy and mass transfer, the electrode degradation mechanisms in the lifespan extension of electrolysis systems, and the key factors in enhancing WE for hydrogen production, providing a comprehensive summary of current research progress. The review focuses on the complex regulatory mechanisms of frequency, duty cycle, amplitude, and other factors in hydrogen evolution reaction (HER) performance within PDE strategies, revealing the interrelationships among them. Finally, the potential future directions and challenges for transitioning from laboratory studies to industrial applications are proposed. Highlights: 1 The mechanisms, key factors, and merits of pulsed dynamic electrolysis (PDE) in energy and mass transfer, extending system lifespan, and enhancing water electrolysis are covered. 2 Synergies and parameter-performance relationships between PDE and hydrogen evolution reaction are emphasized. 3 Future prospects and challenges for the development of PDE technology are outlined.